Sloganization in Language Education Discourse Conceptual Thinking in the Age of Academic Marketization - Breidbach, Stephan; Küster, Lutz; Schmenk, Barbara (Multilingual Matters, 2018)
This volume focuses (self-)critically on sloganization as an emergent phenomenon in language education discourse. Motivated by an increasing uneasiness with a number of widespread concepts in current language education research that have become sloganized, this volume comprises a collection of chapters by international scholars that scrutinize the discourse of language education, identify popular slogans and reconstruct the sloganization processes. It promotes critical self-reflection of scholars and professionals in the field of language education – a field that has widely been dominated by the need to develop innovative approaches and practices, at the expense of self-critical work that attempts to situate the field and its approaches within wider historical, cultural and conceptual contexts
Description based on online resource; title from PDF title page (publisher's Web site, viewed 19. Feb 2019)
Keywords: academic self-promotion; academic writing; Language Education; Language; Marketisation; self-branding; Sloganization; Jargon (Terminology); Language and languages -- Study and teaching; Forschungsrichtung; Slogan; Fremdsprachenunterricht; Aufsatzsammlung